TUTURAN ORANG KASO: TINJAUAN ETNOGRAFI KOMUNIKASI - R. Hery Budhiono (Adabiyyāt: Jurnal Bahasa dan Sastra, 2010)
Utterance is a combination between form (surface structure), meaning (deep structure) and other factors, including culture. Utterance, therefore, has semantic and pragmatic content. It is not only about what is said, but also what it implies. This research is aimed to describe a unique language situation in a certain community-The Kaso. The Kaso people have their own paradigm about language, utterance, and the meaning conveyed. They believe that an utterance is all about the sound which is heard without considering any other things behind it. The point of view of this research is ethnography of communication. What should be mastered to face this kind of community will also be the focus of this research.